Implementation Of Network Device Monitoring System Using Snmp Protocol With Email Notification At Smk N 2 Seluma - Pauzan Sakti; Sapri Sapri; Abdussalam Al Akbar (Penerbit Jurnal Indonesia, 2024)
SMK N 2 Seluma currently has a network and is also connected to the internet network, the computer network is used for teaching and learning activities for students and the work of teachers and education staff, the SMK N 2 Seluma computer network still often occurs disturbances in devices that support networks such as access points (often laptop users connect for a long time and even cannot connect to the network). This research aims to monitor network devices using the SNMP protocol on the SMK N 2 Seluma computer network. The research used an experimental method. In monitoring devices on the SMK N 2 Seluma computer network using the SNMP protocol found in the Nagios application. Nagios monitors devices on the network such as connected or not connected, device memory, device storage (HDD) and other monitoring. In monitoring devices on the network Nagios works well, which can monitor according to the script configured on the main Nagios Core system. For notifications will be sent via email that has been set (admin email) in the form of device down conditions. With the monitoring system using the SNMP protocol, it will make it easier for admins to perform maintenance on the network.